2015
DOI: 10.1111/tops.12175
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Parasites, Political Attitudes, and Cooperation: A Model of How Infection Prevalence Influences Openness and Social Group Formation

Abstract: What is the origin of individual differences in ideology and personality? According to the parasite stress hypothesis, the structure of a society and the values of individuals within it are both influenced by the prevalence of infectious disease within the society's geographical region. High levels of infection threat are associated with more ethnocentric and collectivist social structures and greater adherence to social norms, as well as with socially conservative political ideology and less open but more con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Plenty of studies have simulated the evolution of ingroup bias within the framework of cooperation or altruism. They consistently reported the prevalence of infectious disease within the society's geographical region could influence the evolution of cooperation and the formation of social groups within social networks [24]. Our study also found that the ingroup bias can be evolved in the case of low prevalence of infectious disease within ingroups which supports the hypothesis that ingroup bias is an adaptation to the disease threat posed by outgroup members.…”
Section: Discussionsupporting
confidence: 84%
“…Plenty of studies have simulated the evolution of ingroup bias within the framework of cooperation or altruism. They consistently reported the prevalence of infectious disease within the society's geographical region could influence the evolution of cooperation and the formation of social groups within social networks [24]. Our study also found that the ingroup bias can be evolved in the case of low prevalence of infectious disease within ingroups which supports the hypothesis that ingroup bias is an adaptation to the disease threat posed by outgroup members.…”
Section: Discussionsupporting
confidence: 84%
“…Such environmental varieties make it quite possible for our ancestors to face the ecological condition in which ingroup investment is not optimal and should be reduced ( Thornhill and Fincher, 2014 ). Simulation studies also suggest that ingroup derogation would be evolved if ingroup cooperation has collapsed or it is more beneficial to cooperate with outgroup members ( Fu et al, 2012 ; Brown et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, many of the articles reflect, in one way or another, the fact that climate change is politically and ideological contested. Thus, there is concern with “skepticism,” or more accurately denial, of climate science: Torcello () reflects on the ethics of denial; Ranney and Clark () and McCright, Charters, Dentzman, and Dietz () examine the effect of denial on the public; Brown, Fincher, and Walasek () seek to explain the underlying variables that cause people to acquire the worldviews that render them particularly receptive to denial.…”
Section: Strands Of Inquirymentioning
confidence: 99%
“…Being explicit about the extent of uncertainty thus helps limiting its potentially adverse effect on people's trust in projections. Brown et al (2016) take up another fundamental issue that permeates much of the work on climate change in the cognitive sciences; namely, the role of personal worldviews and ideology. Rather than examining its effects, Brown and colleagues seek to explain the origins of individual differences in ideology.…”
Section: From Fundamentals To Behavioral Modeling: the Articles In Thmentioning
confidence: 99%